North Carolinians and Amendment One: Religious Participation and Individual Voting Practices - King, Joy L (East Carolina University, 2017)
In 2012, North Carolina residents passed the Amendment One Same-Sex Marriage Ban, which made same-sex marriage illegal at the state constitution level. The goal of this study is to use an integrated sociological perspective to examine the micro-level individual factors that impacted North Carolinians' voting behavior on Amendment One, which caused the macro-level structural changes to the state constitution. For this study, special emphasis is placed on the role of religion on North Carolinians' voting behaviors. Using data from the Sociological/Sustainable Tourism Survey, logistic regression analyses are conducted to evaluate the importance of resident's age, gender, race, level of education, and urban or rural residence on their votes or intended votes on Amendment One within the context of religious attendance and religious affiliation. Results indicate that religious attendance, religious affiliation, gender, race, and level of education are significant predictive factors on North Carolinians' votes or intended votes on Amendment One.
Keywords: Voting Behavior; Voting research--North Carolina; Political participation--North Carolina--Religious aspects; Same-sex marriage--Law and legislation--North Carolina